Protective role of mirtazapine in adult female Mecp2+/− mice and patients with Rett syndrome - Flores Gutiérrez, Javier; De Felice, Claudio; Natali, Giulia; Leoncini, Silvia; Signorini, Cinzia; Hayek, Joussef; Tongiorgi, Enrico (Journal of neurodevelopmental disorders, 2020)
Rett syndrome (RTT), an X-linked neurodevelopmental rare disease mainly caused by MECP2-gene mutations, is a prototypic intellectual disability disorder. Reversibility of RTT-like phenotypes in an adult mouse model lacking the Mecp2-gene has given hope of treating the disease at any age. However, adult RTT patients still urge for new treatments. Given the relationship between RTT and monoamine deficiency, we investigated mirtazapine (MTZ), a noradrenergic and specific-serotonergic antidepressant, as a potential treatment. Adult heterozygous-Mecp2 (HET) female mice (6-months old) were treated for 30 days with 10 mg/kg MTZ and assessed for general health, motor skills, motor learning, and anxiety. Motor cortex, somatosensory cortex, and amygdala were analyzed for parvalbumin expression. Eighty RTT adult female patients harboring a pathogenic MECP2 mutation were randomly assigned to treatment to MTZ for insomnia and mood disorders (mean age = 23.1 ± 7.5 years, range = 16-47 years; mean MTZ-treatment duration = 1.64 ± 1.0 years, range = 0.08-5.0 years). Rett clinical severity scale (RCSS) and motor behavior assessment scale (MBAS) were retrospectively analyzed. In HET mice, MTZ preserved motor learning from deterioration and normalized parvalbumin levels in the primary motor cortex. Moreover, MTZ rescued the aberrant open-arm preference behavior observed in HET mice in the elevated plus-maze (EPM) and normalized parvalbumin expression in the barrel cortex. Since whisker clipping also abolished the EPM-related phenotype, we propose it is due to sensory hypersensitivity. In patients, MTZ slowed disease progression or induced significant improvements for 10/16 MBAS-items of the M1 social behavior area: 4/7 items of the M2 oro-facial/respiratory area and 8/14 items of the M3 motor/physical signs area. This study provides the first evidence that long-term treatment of adult female heterozygous Mecp2 mice and adult Rett patients with the antidepressant mirtazapine is well tolerated and that it protects from disease progression and improves motor, sensory, and behavioral symptoms.